2022
DOI: 10.3390/ebj4010001
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Burns: A Brazilian Study

Abstract: During the COVID-19 pandemic, some of the strategies chosen to contain the spread, such as social isolation and use of alcohol-based hand sanitizer, were suspected to increase the risk of domestic accidents, especially burns. The aim of this study was, therefore, to investigate possible differences in epidemiological trends among burned patients admitted to the main referral hospital of the State of Minas Gerais, Brazil, before and during the pandemic. Methods: All categories of new burns admitted at the Burn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…This may be related to the common cultural practice in Brazil of using alcohol for cleaning and the COVID-19 prevention campaigns which encouraged the use of alcohol as an antiseptic cleaning product. Contrastingly, a Brazilian Trauma Unit reported no significant changes in cause of burns in both adults and children [57]. A children's hospital in Turkey reported that 74.2% of paediatric burn admissions were for scalds but did not compare to a pre-COVID cohort to demonstrate change [58].…”
Section: Impact Of Covid-19mentioning
confidence: 91%
See 1 more Smart Citation
“…This may be related to the common cultural practice in Brazil of using alcohol for cleaning and the COVID-19 prevention campaigns which encouraged the use of alcohol as an antiseptic cleaning product. Contrastingly, a Brazilian Trauma Unit reported no significant changes in cause of burns in both adults and children [57]. A children's hospital in Turkey reported that 74.2% of paediatric burn admissions were for scalds but did not compare to a pre-COVID cohort to demonstrate change [58].…”
Section: Impact Of Covid-19mentioning
confidence: 91%
“…Several studies reported that during the COVID-19 pandemic, the proportion of burn injuries sustained at home increased and that, indeed, burns at home accounted for most burn presentations [10,57,75]. This reflected the increased amount of time, which children spent at home during the lockdown period with the closure of childcare and schools.…”
Section: Impact Of Covid-19mentioning
confidence: 99%